Emphasizing the Strategies Hospital Manager Use to Improve Customer Services - Leonard, Delores J. (Insights into Economics and Management Vol. 7, 2021)
The purpose of this study was to explore strategies for hospital managers to improve customer services. The target population consisted of five hospital managers who implement customer services strategies within hospitals. The conceptual framework for the study was the expectation-confirmation theory. Using methodological triangulation, the data derived from included semistructured interviews, hospital policy and procedure documents, and qualitative data from the Consumer Assessment of Healthcare Providers and Systems (HCAHPS) Hospital Compare website. The three major themes were to improve interpersonal communication, address issues in the hospital environment, and provide employee training. The findings reveal that exploring employee training relate to the conceptual framework of the expectation-confirmation theory. Hospitals’ staff exhibit satisfactory performance when customer expectations, regarding the quality of medical care and service satisfaction, receive confirmation. Consistent review of the strategies in the daily operations of the hospital staff will enable hospital managers to continuously increase customer satisfaction and achieve the goal of reaching the 75% level or higher. The participants described multiple attempts to alter operations within the hospital based on customer expectations for satisfaction and to confirm customer satisfaction for the hospital system. The expectation confirmation theory by [1] Joo, Park, and Shin (2017) was the framework of this study. Hospital managers performed actions for example, hiring the right people, using customer feedback for improvement, and using the HCAHPS qualitative data to create strategies that would meet customer expectations for satisfaction and loyalty.